2004
DOI: 10.1111/j.1365-2362.2004.01309.x
|View full text |Cite
|
Sign up to set email alerts
|

Fabry disease defined: baseline clinical manifestations of 366 patients in the Fabry Outcome Survey

Abstract: With the advent of enzyme replacement therapy, it is important that general practitioners and physicians in a range of specialties recognize the signs and symptoms of Fabry disease so that effective treatment can be given. Baseline data from FOS demonstrate that enzyme replacement therapy should not be restricted to hemizygous men, but should be considered for both heterozygous females and children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
626
3
43

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 732 publications
(719 citation statements)
references
References 21 publications
19
626
3
43
Order By: Relevance
“…Several recent studies have shown a high prevalence of Fabry disease in populations with unexplained renal failure [21], [22], [23], [24], stroke [25], [26], [27] or hypertrophic cardiomyopathy [28], [29], [30]. However, screening these populations for Fabry disease is hampered by the low sensitivity of GLA activity measurement in female patients (50% [31]–67% [32]) whereas diagnostic sequencing of the GLA gene is not feasible given the high cost (currently ca. 2,000–3,000 USD).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown a high prevalence of Fabry disease in populations with unexplained renal failure [21], [22], [23], [24], stroke [25], [26], [27] or hypertrophic cardiomyopathy [28], [29], [30]. However, screening these populations for Fabry disease is hampered by the low sensitivity of GLA activity measurement in female patients (50% [31]–67% [32]) whereas diagnostic sequencing of the GLA gene is not feasible given the high cost (currently ca. 2,000–3,000 USD).…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms include dyspnoea in up to 69% of men and 65% of women (Mehta et al 2004), cough, wheeze, reduced exercise tolerance (Lobo et al 2008;Germain 2010) and fatigue (Lobo et al 2008;Franzen et al 2013). Obstructive airway disease has been reported in up to 26% of women and 61% of men (Rosenberg et al 1980;Germain 2010;Franzen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The average age at Fabry disease diagnosis is 29 years for males (Desnick et al 2AA3), years after disease pathology has significantly progressed and potentially darnaged multiple bodily systems (Brady et al 2001;Schiffinann et al, 2001). Although the onset of Fabry disease symptomatology in females may be comparable to males (Ries et al 2003), the average delay in diagnosis is 16.3 years from the onset of symptoms for females, compared with an average of 13.7 years for males (Mehta et al, 2004 (Miles and Huberman 1994). With this technique, themes arise from the raw data, rather than being deductively coded from a pre-determined theory or methodology (Miles and Huberman 1994).…”
Section: Introductionmentioning
confidence: 99%